FINANCIAL BEHAVIOR WITH A CASE-BASED APPROACH ON Y GENERATION MSMEs FOR SUSTAINABLE FINANCE - Liliek Nur Sulistiyowati; Ririh Anggraini Setyahety; Anisa Pratiwi; Yusuf Bachtiar (PENANOMICS: International Journal of Economics, 2023)
In SMEs, financial decisions are largely governed by the attitude of the owner-manager. Owner-managers have a very dominant role in making financial decisions for their business. Having financial literacy skills allows MSME actors to be able to make informed decisions about their funds and minimize mistakes in financial matters. This study tries to analyze financial behavior with a case-based approach to generation Y MSME actors for sustainable finance by using tests of qualitative factors that influence financial decision-making in MSME actors. The analysis technique used in this study uses a qualitative method. Data collection was done using in-depth interviews with Generation Y MSME actors in Madiun City. The resulting research results show that MSMEs have recorded financial reports, even in their simplest form. MSMEs generally only record sales transactions and purchase transactions of goods and calculate MSME business profits. MSMEs have not made a separation between MSME business accounts and the personal accounts of MSME owners. MSMEs have not carried out budget planning when running MSME businesses. The main problem for MSME businesses is the lack of capital for business development.